Pembuatan Sistem Keuangan pada Continuing Education Centre Universitas Kristen Petra - Ryan Kick Kassidy; Silvia Rostianingsih; Agustinus Noertjahyana (Jurnal Infra, 2016)
Continuing Education Centre is an unit engaged in education services under coordination of Vice Rector Academic Petra Christian University. Continuing Education Centre is qualified for continuing education with variety in their programs. Until now, Continuing Education Centre doesn’t have a system that helps its transaction process so mistakes often made in transaction process. Therefore, in this thesis will be made accounting information system and the estimated expenditure programs, which help the Continuing Education Centre in processing transactions and records them into useful reports for Continuing Education Centre.The process of making this system starts from analyzing the needs of the company, making the design system using Data Flow Diagram and Entity Relational Diagram. The system is built using the MySQL database and Hypertext Prepocessor (PHP). Scope of the development includes transaction recording, scheduling and estimation, manufacture of Chart of Accounts, manufacture of transaction expenses, as well as the manufacture of journals and reports automatically. All of these are supported using a VPN server based on Windows 7 OS and website interface.Test result shows the programs are able to assist in processing transactions, forecasting and producing reports which useful for the finance of Continuing Education Centre. According to the questionnaire, it is proven to be able fulfilling the company needs with satisfaction level of 66.66% are pleased and 33.33% are adequate.